“Analysis of the use of closed task in learning process in students of 10th class “A” at Unidad Educativa “Quislag”, Alausi city during the academic period 2015-2016”. - Paca Paltan, Rosa Matilde (2017)
This research was carried out with the teacher and students of Décimo Año de Educación General Básica class “A” Unidad Educativa de Educación Básica “QUISLAG” located in Tixán- Alausí in Chimborazo province, during the academic period 2015-2016.” The main purpose of this research was to describe the use of Closed Tasks to improve the English learning process of English as a foreign language. This study is exploratory with a qualitative approach, which used the ethnographic and hermeneutic method to describe, analyze and interpret the gathered information based on the theoretical foundation of the study. The population of this research was built up by 20 students and 1 teacher. For the data collection, it was used the observation technique which was applied in some regular English classes to the population, in order to identify all the difficulties faced by students in the learning process. The data collection instrument was carefully designed considering the main characteristics of Closed Tasks stated in the theoretical framework. The results evidenced that the teacher uses Closed Tasks to teach English, but the methodology is not properly applied, in consequence the learning goals are not reached.